Persepsi Guru Matematika terhadap Implementasi Kurikulum 2013 dalam Pembelajaran Matematika di SMP - Kusumah, Siska Nurfadilah Sri; Yusritawati, Ita; Nabilah, Azhar; Rahayu, Ika Sri; Sulastri, Nina (Indo-MathEdu Intellectuals Journal, 2024)
The 2013 curriculum includes several changes in the teaching and learning process. School conditions (principals, teachers, administrative staff, and students) have different enthusiasms, even feeling unprepared for the curriculum changes. The purpose of this study is to determine the perception of mathematics teachers regarding how the 2013 curriculum is implemented in the learning process. The data collection method used is qualitative descriptive in a natural setting, using interview methods, filling out questionnaires by respondents and documentation. Purposive sampling techniques were used in determining research subjects, The subjects in this study were mathematics teachers who taught in class IX from several schools in Kuningan Regency, consisting of MTs Negeri 3 Kuningan, SMP Negeri 7 Kuningan, and SMP Negeri 1 Kadugede. From the results of the questionnaire, the average teacher response was obtained, including resource person F, who received an average of 95%. Interviewee S with an average of 65%, and source Y with an average of 69%. The overall average of the teacher perception questionnaire was 76%, this shows that the 2013 curriculum has been implemented well and effectively to support mathematics learning. This study revealed that the implementation of the 2013 curriculum for mathematics in class IX was effective, but it was time consuming for teachers to provide the material to students, causing them to be less involved in researching the material and focusing more on interactivity